Application of mobilizing extra-training means in process of pre-start martial arts sportsmen`s training (on example of fencing) - Lopatenko, G. O.; Tumanova, V. N.; Gatsko, E. V. (Physical Education of Students, 2015)
Purpose: to test experimentally influence of worked out extra-training means` complex on functional potentials of elite fencers. Material: in the research 12 qualified sportsmen participated. Changes in cardio-respiratory system`s responses were detected by training impulse. Results: application of experimental complex resulted in increase of training impulse by 1.94 conv.un., than traditional sportsmen`s warming up. With usage of experimental complex sportsmen fulfilled, in average, 64.4% of work in zones of sub-maximal and maximal intensity. Restoration of heart beats rate of all sportsmen was within standard requirements (restoration of 120 b.p.m. during 3 minutes). In conditions of traditional warming up sportsmen fulfilled, in average, 71.2% of work with low or moderate intensity. Conclusions: the offered complex of extra-training influences increase effectiveness of pre-start warming up, raise organism`s potentials for realization of available functional potential.